Breast milk feeding: Trials and tribulations of Indian mothers having infants with cleft lip and palate - Deepthi J. Koppal; V. Manaswini; Sandra Jeswika Fernandes; Neha Grace Benny (Wolters Kluwer Medknow Publications, 2024)
Background: Breastfeeding infants with a cleft is difficult due to underlying anatomical deficits. The success of breastmilk feeding in this population is highly dependent on the mother. Nevertheless, the rate and duration of breastmilk feeding are often poor in this population due to early cessation of breastmilk production. These infants are therefore at high risk for "failure to thrive". Aim: The study aimed to identify the challenges encountered by mothers having infants with cleft in establishing and maintaining breastmilk production. Objective: To explore the factors that impact establishing and maintaining breastmilk production viz., a) Mother-infant separation b) Access to Lactation and Feeding consultation c) Breastmilk expression strategies d) Formula supplementation rate e) Motivating or demotivating factors to breastmilk feeding. Method: This study was a phone survey conducted on 28 mothers who had availed lactation and feeding consultations between 2019 and 2020. Results: Various factors impacting the onset and establishment of breastmilk feeding noted were, separation of mother and infant at birth and the duration of separation, lack of access to professional help in lactation and feeding during stay in hospital, irregular and inappropriate breast milk expression, early formula supplementation demotivation due to various lactation and feeding challenges. Conclusion: Support from healthcare professionals specialized in lactation and feeding consultation for mothers having infants with cleft particularly, Speech Pathologists, Nursing staff and Lactation Consultants is critical to increase the rate and duration of breastmilk feeding. Breastmilk feeding should be thus prioritized and supported to enable infants with cleft to thrive.